Legal medicine implications of a multidisciplinary approach to managing Traumatic Encephalopathy Syndrome in Australia - Kim, Peter S.; Beran, Roy G. (Frontiers in Neurology, 2023)
The medical profession has a fundamental obligation to accurately diagnose and effectively treat a range of diseases and conditions. In the case of Traumatic Encephalopathy Syndrome (TES), where there are no universally accepted clinical diagnostic criteria, a clear clinical diagnosis can pose significant challenges for healthcare providers and for subsequent appropriate management. “Nihilism” or an uncertain working diagnosis is not acceptable in the medical field and deserves further consideration. This paper explores the legal obligations that are placed upon healthcare professionals, both individually and as a part of a multidisciplinary team. This article analyses the responsibilities and expectations of medical professionals in diagnosing and treating complex medical conditions, such as TES. The authors address legal issues that must be considered for an effective operation of integrated medicine to enhance the overall quality of care and improving patient outcomes for those affected with underlying Chronic Traumatic Encephalopathy (CTE).